TANGO-2 with Severe and Prolonged Rhabdomyolysis in a 2-year Old Male TANGO-2 with Severe and Prolonged Rhabdomyolysis in a 2-year Old Male with Human metapneumovirus Infection. A case report and literature review. : TANGO-2 (Translation: The University of Toledo Journal of Medical Sciences, 2020)
We report a unique case of prolonged acute rhabdomyolysis in a 2-year-old male with known TANGO-2 mutation with delayed peak in creatinine kinase levels secondary to human metapneumovirus infection. Creatinine kinase peaked at 424,760 U/l on day 9 of hospitalization. Resolution of rhabdomyolysis was achieved using aggressive management with intravenous fluids with optimal urine output and no kidney injury.  TANGO-2 patients may develop severe and prolonged rhabdomyolysis with a delayed peak suggesting the need for prolonged inpatient hospitalization to prevent life-threatening complications.
Keywords: TANGO-2, Rhabdomyolysis, creatinine kinase